Tax Administration and Timely Payments: A study of selected State Internal Revenue Service in South-West Nigeria - Modupeola Morenike, Adesemowo; Chukwudi, Celestina Ekene; Bello, Wasiu Olaide (PERSPEKTIF, 2024)
This study examined the effect of tax administration and timely payments: a study of selected Internal Revenue Service in South-West Nigeria. A field survey research method was adopted, primary data obtained through the administration of a structured questionnaire was used and the hypotheses were tested using regression analysis. The population of the study consisted of 4499 members of staff in the tax revenue office in South-West Nigeria. Three hundred and eighty-seven copies of questionnaires were administered while 382 (98.7%) were retrieved. The findings of the study revealed that the tax administration of the selected State Internal Revenue Services has a significant effect on timely payments (Adj.R2 = 0.115, F(3, 383) = 17.405), p < 0.05). The study concluded that a significant relationship exists between Tax administration measured as Tax assessment (TASS), Tax remittance (TREM) and Tax collection (TCOL), and Timely Payments of taxpayers’ declarations of selected State Internal Revenue Services in South-West Nigeria. The study recommended that State tax authorities should restructure their tax administration system to increase their efficiency and effectiveness in tax assessment, tax collection, and tax remittance that will provide adequate and relevant training for members of staff on the use of information technology and update the technological equipment’s used so that the members of staff can be technologically competent. Technological devices should be made available to staff members in the various tax stations outside the head office.